The notion numerical growth in mathematics textbooks and periodic publications between two word wars - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2009)
Analysis the notion numerical growth in mathematics textbooks and periodic publications between two word wars is presentedin this article. The differentnumerical notion in mathematics textbooks is described. The necessity notion numerical growth in periodic publications is introduced. The opinions and examples are analyzed. The object of the research – The research the notion numerical growth in mathematics textbooks and periodic publications between two word wars. The research tasks: 1. The discuss numerical notions shall advance supposition on the mathematics teaching. 2. Reintroduce the numerical notion representable extension methodical reference between two word wars in Lithuania. 3. Analyze number notion lead method in arithmetic textbooks between two word wars in Lithuania. The purpose of investigation: investigate numerical notions shall growth in the introduction in periodic publication and arithmetic textbooks. Conclusions: 1. The periodicals in between two word wars the numerical notion growth earmark large attention. 2. The numerical notion representable imaginatively in different arithmetic’s textbooks in between two word wars.